A Note on Statistical Limit and Cluster Points of The Arithmetical Functions ap(n), Î³(n), and Ï„(n) in The Sense of Density - Adem, Abdu Awel; Kucukaslan, Mehmet (Journal of the Indonesian Mathematical Society, 2020)
In this paper, by using natural density of subsets of N, the statistical limit and cluster points of the arithmetical functions (ap (n)), Î³ (n),Ï„(n), Î” Î³ (n) and Î” Ï„ (n) are studied. In addition to this, we also investigate statistical limit and cluster points of (Î” r Î³ (n) and (Î” r Ï„ (n)) for each r Ä±n N.